2019
DOI: 10.1016/j.gore.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions of gynecologic oncology fellows on readiness for subspecialty training following OB/GYNRESIDENCY

Abstract: A recent survey of fellowship program directors (PD) within gynecologic oncology (GO) noted concerns regarding the abilities of incoming fellows. The objective of this study was to evaluate the perceptions of current and former fellows in gynecologic oncology of their readiness for fellowship training. A previously used survey was modified and distributed in 2016 to current and former fellows in GO. The survey explored domains of independent practice, psychomotor ability, clinical evaluation and scholarship. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recent studies have documented gaps in learning among gynecologic oncology fellows. Graduating fellows risk being unprepared for dealing with postoperative complications, developing management plans, and executing palliative care principles [6][7][8]. To address these gaps and better develop graduated autonomy in the outpatient arena, some training programs employ a fellow-run clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have documented gaps in learning among gynecologic oncology fellows. Graduating fellows risk being unprepared for dealing with postoperative complications, developing management plans, and executing palliative care principles [6][7][8]. To address these gaps and better develop graduated autonomy in the outpatient arena, some training programs employ a fellow-run clinic.…”
Section: Introductionmentioning
confidence: 99%
“…When surveyed on preparedness post residency, 28.2% of obstetrics and gynecology (OBGYN) graduates reported a lack of confidence in their surgical skills. 1 Similarly, a survey of fellowship program directors found that residents' surgical skills were deficient, and they were not adequately prepared for fellowship training. 2 This further highlights the importance of optimizing resident surgical training.…”
Section: Introductionmentioning
confidence: 99%